Evaluation of the Practice of Tax Consultant Services Related to Corporate Tax Disclosure in the Tax Audit Process - Revanty Iryani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
With the increasing number of companies in Indonesia that meet the criteria for tax audits by the Regulation of the Minister of Finance Number 17/PMK.03/2013 Article 4 requires companies to be able to disclose their tax policies during the tax audit process. This has resulted in more and more companies in Indonesia using the services of tax consultants to assist the Company in disclosing tax policies in the Tax Audit process. In this study, researchers evaluate the services of tax consultants in providing consulting services to companies related to the disclosure of tax policies during the Tax Audit process in Indonesia and whether the results of the Tax Audit on this disclosure ultimately benefit the Company in which the benefit is measured by the reduction in the amount of the Company's tax payment obligations. The method used in this research is a case study by interviewing Tax Consultants and companies' internal tax managers and conducting documentation analysis. This study ultimately concluded that using the services of Tax Consultants during the Tax Audit process has decreased Company's tax obligation. This research is expected to benefit the taxation sector in Indonesia, especially tax consultants in advising companies in Indonesia. This research is also expected to benefit academic researchers, organizations and institutions.